2017
DOI: 10.1080/00084433.2017.1345059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro-pores on cracks formation in metallurgical coke

Abstract: The relationships of micro-pores and cracks in metallurgical coke have been investigated by optical microscope and FESEM, using surface section samples. The pores have circular, elliptical and irregular shapes with smooth outlines, formed during the thermoplastic stage of the coking process. They often associate with connecting cracks between neighbouring pores. In case of elliptical pores, the connecting cracks are usually oriented along the longer axis of the pore. The connecting cracks can be developed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…He found that slight roundness and large distorted pores might cause stress concentration and significantly reduce the strength of coke. Gornostayev et al [ 24 ] found a similar result by directly observing the coke using a scanning electron microscope. The elliptical, elongated, and flattened pores, compared with circular pores, showed a lower ability to resist load pressure.…”
Section: Relations Between Coke Structures and Propertiesmentioning
confidence: 67%
See 1 more Smart Citation
“…He found that slight roundness and large distorted pores might cause stress concentration and significantly reduce the strength of coke. Gornostayev et al [ 24 ] found a similar result by directly observing the coke using a scanning electron microscope. The elliptical, elongated, and flattened pores, compared with circular pores, showed a lower ability to resist load pressure.…”
Section: Relations Between Coke Structures and Propertiesmentioning
confidence: 67%
“…In this process, the structures of the coke change significantly [ 18 ]. It is well known that the reactivity [ 19 , 20 ] and the strength of coke [ 21 , 22 , 23 , 24 ] are closely related to its structures. Therefore, it is essential to characterize the coke structures comprehensively.…”
Section: Introductionmentioning
confidence: 99%